Hospital pharmacists', doctors' and nurses' perceptions of intra- and inter- professional communication in the context of electronic prescribing and medication administration systems: A qualitative study. - Soomal Mohsin-Shaikh; Ann Blandford; Bryony Dean Franklin (PLoS ONE, 2023)
Background Effective, integrated and coordinated communication is essential in providing high quality patient care. Little prior research has detailed the impact of electronic prescribing and medication administration (ePMA) systems on healthcare professionals' (HCPs') communication. We investigated hospital pharmacists', doctors' and nurses' perceptions of how ePMA systems have affected, or are expected to affect, the way they communicate with each other in an inpatient setting. Methods A qualitative study in three English NHS hospitals: two used different inpatient ePMA systems, and one used paper-based prescribing. We conducted focus groups with pharmacists, and semi-structured individual interviews with doctors and nurses. Transcribed data were analysed inductively using thematic analysis. Results Nine focus groups, three at each hospital, were conducted with pharmacists with different levels of seniority (58 pharmacists in total). Fourteen doctors and twelve nurses took part in individual interviews. Four themes were generated: modes of communication, reduced pharmacist visibility, system limitations, and future aspirations for ePMA. Whether working with ePMA or paper-based systems, all participants preferred to communicate face-to-face to facilitate collaborative discussions regarding patient care. Participants perceived that ePMA reduced contact time with patients. Pharmacists perceived that both their physical ward presence and their written communication on medication charts had reduced since introduction of ePMA. Doctors felt they were now less likely to ask pharmacists questions due to pharmacists' reduced physical presence on the ward. Hardware and software limitations were identified by all HCPs, with suggestions made for future developments to better support communication. Conclusion ePMA does not necessarily support communication among HCPs. Pharmacists and doctors were also concerned that ePMA reduces communication between themselves and their patients. Hospital managers should ensure sufficient hardware for HCPs, including pharmacists, to conduct their work in clinical areas, and work with ePMA system suppliers to develop ways of enhancing, rather than inhibiting, communication.